Dissociation between hypertrophy and fibrosis in the left ventricle early after experimental kidney transplantation. Issue 3 (March 2020) - Krebber, Merle M.; Papazova, Diana A.; Oosterhuis, Nynke R.; Mokry, Michal; Cramer, Maarten J.; Cheng, Caroline; Joles, Jaap A.; Verhaar, Marianne C.
Abstract : Objective: Left ventricular (LV) hypertrophy is the most common cardiac alteration in patients with chronic kidney disease (CKD). Normalization of hypertension in CKD patients receiving a healthy kidney allograft often reverses LV hypertrophy, but effects on LV fibrosis remain unclear. To study causal interactions between graft and environment on LV hypertrophy, fibrosis and inflammation, we applied cross-kidney transplantation Methods: Orthotopic transplantation was performed after inducing CKD in rats by two-third bilateral ablation of kidney mass: Healthy kidney (K) donor to healthy heart (H) recipient (healthy-K→healthy-H); CKD-K→healthy-H; healthy-K→CKD-H; CKD-K→CKD-H; N = 6 per group. Results: At week 6 after transplantation, mean arterial pressure (MAP) and LV mass index (LVMI) increased in CKD-K versus healthy-K irrespective of recipient. Contrarily, LV fibrosis was more severe in CKD-H versus healthy-H recipients irrespective of graft. Indeed, MAP and plasma creatinine correlated with LVMI but not with LV fibrosis. Increased LVMI in CKD-K→CKD-H not accompanied by cardiomyocyte cross-sectional area gain is consistent with eccentric remodelling. Cardiac RNA sequencing found a strong transcriptional response associated with LV fibrosis but only sparse changes associated with LV hypertrophy. This response was, among others, characterized by changes in extracellular matrix (ECM) and inflammatory gene expression. Conclusion: LVMI reversed and MAP and renal function were normalized early after transplantation of a healthy kidney. However, LV fibrosis persisted, dissociating LV hypertrophy from LV fibrosis within 6 weeks. Elucidating cardiac ECM dynamics in CKD patients, although challenging, appears promising. Abstract : Supplemental Digital Content is available in the text